Modification of Angry Emotion Behavior in 5 Years Old Children with Relaxation and Self-Management Procedures in Kindergarten - Yulianti, Enny; Afrianingsih, Anita (Al Hikmah: Journal of Education, 2022)
This study aims to modify the elimination of angry behavior in children aged 5-6 years with relaxation and self-management procedures in TK/TA Panggang. This type of research is qualitative. The data in this research are school identity, student profiles, and those related to learning activities. Data collection techniques and instruments include observation, interviews, and documentation. The data analysis technique is data reduction technique, data display, conclusion or verification. The results of the relaxation technique can have a positive impact on the child, so that angry behavior can be relaxed, because if the child repeats negative behavior it will be sanctioned and vice versa if the child behaves positively will be given a positive surprise so the child will get used to and avoid negative behavior.